"B" is for Betsy - Haywood, Carolyn, 1898-1990. (New York : Harcourt, Brace and Company, 1939)
Betsy experiences an interesting first year in school and looks forward to summer vacation at her grandfather's farm.
Accelerated Reader AR
Keywords: First grade (Education) -- Fiction; Intergenerational relations -- Fiction; Girls -- Conduct of life -- Fiction; Conduct of life -- Fiction; Schools -- Fiction; Students -- Fiction; Farms -- Fiction; Juvenile fiction